2022
DOI: 10.3390/s22176694
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Derived Lifting Techniques and Pain Self-Efficacy in People with Chronic Low Back Pain

Abstract: This paper proposes an innovative methodology for finding how many lifting techniques people with chronic low back pain (CLBP) can demonstrate with camera data collected from 115 participants. The system employs a feature extraction algorithm to calculate the knee, trunk and hip range of motion in the sagittal plane, Ward’s method, a combination of K-means and Ensemble clustering method for classification algorithm, and Bayesian neural network to validate the result of Ward’s method and the combination of K-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Selecting the optimal number of clusters for a given dataset is challenging. One common strategy for finding the optimal number of clusters is calculating the average silhouette score among the criteria used in the optimization process [ 22 ]. The silhouette method was used to determine the similarity within the cluster of each data point and the distance between other clusters [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Selecting the optimal number of clusters for a given dataset is challenging. One common strategy for finding the optimal number of clusters is calculating the average silhouette score among the criteria used in the optimization process [ 22 ]. The silhouette method was used to determine the similarity within the cluster of each data point and the distance between other clusters [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…One common strategy for finding the optimal number of clusters is calculating the average silhouette score among the criteria used in the optimization process [ 22 ]. The silhouette method was used to determine the similarity within the cluster of each data point and the distance between other clusters [ 22 , 23 ]. The silhouette scores range from 0 to 1, with higher scores indicating better cluster categorization and lower scores indicating poorer cluster categorization [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recent technological advancements, such as motion capture systems and machine learning algorithms, have shown great potential in objectively identifying and correcting movement patterns during lifting tasks or patient flow [ 7 , 8 ]. Motion capture systems can capture detailed movement data during lifting tasks, including joint angles and velocity.…”
Section: Introductionmentioning
confidence: 99%
“…There are two main applications of machine learning: classification and regression. Recent research has presented the potential of machine learning in clustering lifting movements in people with LBP and healthy people [ 7 ] or classifying thyroid disease [ 9 ]. Regression analysis is a commonly used statistical technique for modelling the associations among variables.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, machine learning identified that simple kinematic indicators were sensitive to low-back pain and therefore could gradually be used by clinicians in the assessment of CLBP patients. Machine learning can even go beyond binary classification in CLBP patients, as shown in [ 11 ]. From the video analysis of 115 CLBP participants lifting an 8 kg weight, Ward clustering suggests that there are four different lifting techniques in people with CLBP.…”
mentioning
confidence: 99%